2004
DOI: 10.1074/jbc.m402273200
|View full text |Cite
|
Sign up to set email alerts
|

A M55V Polymorphism in a Novel SUMO Gene (SUMO-4) Differentially Activates Heat Shock Transcription Factors and Is Associated with Susceptibility to Type I Diabetes Mellitus

Abstract: Three SUMO (small ubiquitin-related modifier) genes have been identified in humans, which tag proteins to modulate subcellular localization and/or enhance protein stability and activity. We report the identification of a novel intronless SUMO gene, SUMO-4, that encodes a 95-amino acid protein having an 86% amino acid homology with SUMO-2. In contrast to SUMO-2, which is highly expressed in all of the tissues examined, SUMO-4 mRNA was detected mainly in the kidney. A single nucleotide polymorphism was detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
265
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(273 citation statements)
references
References 22 publications
4
265
0
4
Order By: Relevance
“…For the putative causative variant 163A4G, Owerbach et al report increased transmission of the A allele to T1D affecteds while Guo et al observe increased transmission of the G allele; although of opposite polarity, both findings were significant. 18,24 While Guo et al reported increased NFkB transcriptional activity in association with the G allele, no significant allele specific variation in such activity was observed in a separate report by Bohren et al 25 While the predicted effects of variants in the TAB2/ SUMO4 locus on NFkB activity are mediated through biochemical interactions with other molecules, Karban et al 26 have described a functional insertion/deletion (indel) polymorphism that directly affects the expression of NFkB. The deletion allele at position À94 in the promoter of the NFKB1 gene displayed reduced binding of proteins from nuclear extracts of specific tissues in mobility shift assays and reduced transcription in luciferase assays compared to the insertion allele.…”
Section: Introductionmentioning
confidence: 93%
“…For the putative causative variant 163A4G, Owerbach et al report increased transmission of the A allele to T1D affecteds while Guo et al observe increased transmission of the G allele; although of opposite polarity, both findings were significant. 18,24 While Guo et al reported increased NFkB transcriptional activity in association with the G allele, no significant allele specific variation in such activity was observed in a separate report by Bohren et al 25 While the predicted effects of variants in the TAB2/ SUMO4 locus on NFkB activity are mediated through biochemical interactions with other molecules, Karban et al 26 have described a functional insertion/deletion (indel) polymorphism that directly affects the expression of NFkB. The deletion allele at position À94 in the promoter of the NFKB1 gene displayed reduced binding of proteins from nuclear extracts of specific tissues in mobility shift assays and reduced transcription in luciferase assays compared to the insertion allele.…”
Section: Introductionmentioning
confidence: 93%
“…Three different SUMO proteins (B11 kDa) were identified in mammalian cells: SUMO-1, SUMO-2 and SUMO-3, with SUMO-2 and SUMO-3 having very high sequence similarity (Hay, 2005). A tissue-specific SUMO-4 has also been recently identified, with sequence homology to SUMO-2/3 (Bohren et al, 2004). SUMO modification consists in the covalent attachment of SUMO to a lysine residue, that generally lies within the consensus motif j-K-x-D/E (Rodriguez et al, 2001;Sampson et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In vertebrates there are at least three additional proteins. SUMO-2 and SUMO-3 are ϳ45% identical to SUMO-1 (Saitoh and Hinchey, 2000), and SUMO-4 shows an 86% amino acid homology to SUMO-2 (Bohren et al, 2004). SUMO is conjugated to protein substrates via an ATP-dependent enzymatic pathway that is mechanistically similar to ubiquitination.…”
Section: Introductionmentioning
confidence: 99%